Menetrier’s disease - Gonzalez Villar, Marco Antonio; Hernandez Valdez, Gustavo Adolfo; Medina Jimenez, Ivan Alejandro; Alcaraz Palomares, Angel Gibran; Contreras Escamilla, Juan Antonio (International Journal of Research in Medical Sciences, 2024)
A clinical case of a 57-year-old female patient with history of epilepsy diagnosed in childhood, currently being treated with magnesium valproate, she presented with oral intolerance, ascites and weight loss. The initial laboratory workup was significant for hypoalbuminemia (serum albumin 18 g/L), but her liver and renal function were normal and urinalysis was negative. Panendoscopy was performed with a microscopic report: histopathology reporting findings related to hypertrophic gastropathy, gastric foveolar hyperplasia, with chronic diffuse moderate edematous gastritis without data of acute activity, with Helicobacter pylori bacilli in small quantity (+), negative for metaplasia, dysplasia and/or malignancy compatible with Menetrier disease. The patient was evaluated by the general surgery service to perform a jejunostomy and/or total gastrectomy as an adjuvant treatment for the patient. The extent of the gastrectomy to be performed is the subject of debate. The patient refused surgical treatment, so she was voluntarily discharged to an outpatient clinic to begin monoclonal treatment. The patient died 3 weeks before starting monoclonal treatment. Therefore, untreated patients have a high mortality rate due to complications.